The concept and significance of forensic characteristics of the unlawful seizure of enterprise, institution or organisation property (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The unlawful seizure of property of an enterprise, institution or organisation is a fairly common criminal offence in the field of business activity. This criminal offence causes economic losses to both business entities and the state as a whole, reduces the level of economic security and, as a result, the level of investment, discredits the work of government agencies, undermines the authority of the state at the international level, etc. In order to overcome and prevent economic risks, it is necessary to develop a methodology for investigating a criminal offence under Article 206-2 of the Criminal Code of Ukraine.The purpose of the study is to define the concept of “forensic characteristic of unlawful seizure of enterprise, institution or organisation property”, to clarify the role of such forensic characteristic in the methodology of investigation of this criminal offence, and also to establish the sources of information for the purpose of forming a forensic characteristic. To achieve the stated purpose of the study, a thorough analysis of the scientific forensic literature, the results of investigative and judicial practice has been carried out.In the process of summarising the views of scholars, the article establishes that the main, basic, initial element of the forensic methodology is the forensic characteristic of the criminal offence under study. Based on the results of a comprehensive analysis, it has been established that the forensic characteristic of unlawful seizure of property of an enterprise, institution or organisation should be considered an information model of this criminal offence which consists of a set of generalized information about its interrelated forensically significant features.With regard to the importance of forming a forensic characteristic, two directions of its use have been distinguished i.e., theoretical and practical.The article analyses the sources of obtaining the information necessary for forming a forensic characteristic of the unlawful seizure of property of an enterprise, institution or organisation, and as a result of this analysis, two main sources of information are identified: documents and persons.